Toward 2D van der Waals Entropy Mixture MX2 (M = Mo, W; X = S, Se, Te) for Hydrogen Evolution Electrocatalysis - Paštika, Jan; Güngen, Deniz; Subramani, Amutha; Mazánek, Vlastimil; Serra, Marco; Zeng, Lunjie; Olsson, Eva; Gusmão, Rui; Sofer, Zdeněk (ACS applied materials & interfaces, 2025)
High-entropy alloys have emerged as a class of materials, offering unique properties due to their irregular and randomized arrangement of multiple elements in an ordered lattice. This concept has been extended to two-dimensional (2D) van der Waals materials, including transition metal dichalcogenides (TMD), which exhibit promising applications in electrocatalysis. In this work, we have explored the synthesis of entropy mixture crystals (TMDmix) involving the chemical vapor transport of five individual elements, Mo and W as metal elements, S, Se, and Te as chalcogenide elements, resulting in a crystalline structure with a controlled composition Mo0.56W0.44(S0.33Se0.35Te0.32)2, with an estimated ΔSmix of 0.96R. When observed along the [001] zone axis, STEM HAADF images indicate the presence of the different crystal phases of the 2D TMDs (1T, 2H, and 3R). Our findings demonstrate the potential of the entropy TMDmix materials as catalysts for the hydrogen evolution reaction, offering an alternative to noble metal-based catalysts. To maximize the potential of TMDmix, we chose chemical exfoliation with the resulting material being subdivided into size groups, big and small, according to their lateral size. In an acidic medium, the lowest overpotential of 127 mV and a Tafel slope of 79 mV/dec were obtained for the exfoliated sample with a small lateral size (exf-TMDsmall).
Keywords: 2D material; High Entropy Alloys; Hydrogen Evolution Reaction; Electrocatalysis; Transition Metal Dichalcogenide